Iridium-catalyzed asymmetric allylic substitution reactions - Cheng, Qiang; Helmchen, Günter (Chemical reviews, 2019)
In this review, we summarize the origin and advancements of iridium-catalyzed asymmetric allylic substitution reactions during the past two decades. Since the first report in 1997, Ir-catalyzed asymmetric allylic substitution reactions have attracted intense attention due to their exceptionally high regio- and enantioselectivities. Ir-catalyzed asymmetric allylic substitution reactions have been significantly developed in recent years in many respects, including ligand development, mechanistic understanding, substrate scope, and application in the synthesis of complex functional molecules. In this review, an explicit outline of ligands, mechanism, scope of nucleophiles, and applications is presented.
Publication date (web): December 24, 2018
Gesehen am 23.04.2019